Effect of Different Cleaning Methods on Bond Strength of Resin to Saliva-Contaminated Zirconia: A Systematic Review and Meta-analysis of in Vitro Studies - Alireza Sarraf Shirazi; Sara Majidinia; Tahereh Parhizkar
Background: Saliva contamination during the try-in procedure is one of the leading causes of decreased bond strength of resin to zirconia. In this meta-analysis, we evaluated the effects of different cleaning methods on the bond strength of the zirconia restoration. Methods: A systematic search was performed through MEDLINE via PubMed, EMBASE, Scopus, ISI web of knowledge, and Cochrane databases. In vitro articles in which the cleaning methods were compared with contaminated and non-contaminated surfaces were selected for this study. The duration of storage was separated into two subgroups of <1 and >1 week. Results: Out of 909 results of database searches, 15 studies were included in the systematic review. In the storage period of <1 week, there were significant differences between the saliva-contaminated, decontamination with air abrasion (SDM: 2.478, P<0.01), and Ivoclean (SDM: 3.055, P<0.01) groups. Also, in the storage period of >1 week, significant differences were observed between air abrasion (SDM: 2.714, P<0.01), Ivoclean (SDM: 2.575, P<0.01), and argon plasma (SDM: 1.998, P<0.01) groups. There was a significant difference between non-contaminated and isopropanol (<1 week storage period: SDM: −3.252, P=0.05; >1 week storage period; SDM: −1.302, P<0.01) and phosphoric acid (<1 week storage period: SDM: −1.584, P<0.01; storage period >1 week; SDM: −2.021, P<0.01) decontaminated groups. Conclusion: Sandblasting with airborne-particle abrasion (Al2O3), Ivoclean, and argon plasma has been effective in recovering the bond strength of resin to saliva-contaminated zirconia, while bond strength of decontaminated surface with alcohol and phosphoric acid is significantly weaker than in non-contaminated situations.